2022
DOI: 10.3390/ijms232012081
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Changes and Chromatin Reorganization in Brain Function: Lessons from Fear Memory Ensemble and Alzheimer’s Disease

Abstract: Healthy brain functioning in mammals requires a continuous fine-tuning of gene expression. Accumulating evidence over the last three decades demonstrates that epigenetic mechanisms and dynamic changes in chromatin organization are critical components during the control of gene transcription in neural cells. Recent genome-wide analyses show that the regulation of brain genes requires the contribution of both promoter and long-distance enhancer elements, which must functionally interact with upregulated gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 161 publications
0
5
0
Order By: Relevance
“…Healthy brain functioning requires fine control of gene expression in neural cells. Epigenetic regulatory mechanisms and chromatin remodeling are also crucial for cognitive functions such as learning and memory, which involve specific gene expression profiles that are necessary to ensure neural connectivity and plasticity [ 85 , 86 ].…”
Section: Bet Proteins In Brain Physiologymentioning
confidence: 99%
“…Healthy brain functioning requires fine control of gene expression in neural cells. Epigenetic regulatory mechanisms and chromatin remodeling are also crucial for cognitive functions such as learning and memory, which involve specific gene expression profiles that are necessary to ensure neural connectivity and plasticity [ 85 , 86 ].…”
Section: Bet Proteins In Brain Physiologymentioning
confidence: 99%
“…Emerging studies have shown that the multilayered profiles of epigenetic dysregulation, such as DNA methylation, histone modifications, chromatin remodeling, and non-coding RNA regulation, are intimately involved in various complex disease pathogenesis [92][93][94][95], including neurological diseases [31,[96][97][98]. It is known that along with the impact of environmental factors, genetic pre-disposition plays an important role in the epigenetic changes associated with various pathologies [39,46].…”
Section: Discussionmentioning
confidence: 99%
“…As technology improves, more and more studies show that epigenetic mechanisms, such as DNA methylation, histone post-translational modifications and microRNA-mediated post-transcriptional gene regulation, are involved in the pathogenesis of AD and thus influence the onset and progression of AD ( Hernaiz et al, 2022 ; van Zundert and Montecino, 2022 ).…”
Section: Key Mechanisms Of Altered Ahn In Alzheimer’s Diseasementioning
confidence: 99%